Implications of bilateral free trade agreements on access to medicines - Correa Carlos María (The World Health Organization, 2006)
The TRIPS Agreement of the World Trade Organization (WTO) mandated the introduction of protection of intellectual property rights, notably patents, for pharmaceutical products. While the implications for the access to medicines contained in the terms of this Agreement raised significant concerns, a recent new wave of free trade agreements, negotiated outside the WTO, requires even higher levels of intellectual property protection for medicines than those mandated by that Agreement. The measures involved include the extension of the patent term beyond 20 years; prohibition of use of test data on drug efficacy and safety for certain periods for the approval of generic products; the linkage between drug registration and patent protection; in some cases, limitations to the grounds for granting compulsory licences. This article reviews some of these measures that further limit the competition of generic products and discusses their possible implication for access to medicines.